Analisis Tantangan Pembentukan Karakter Siswa Sekolah Dasar melalui Media Sosial - M. Bahrul Ulum; Meilan Tri Wuryani; Mar’atul Faida (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The rapid growth of TikTok has created challenges in shaping the character of elementary school students in the digital era. This study investigates teachers' challenges, character-building strategies, and the character values most affected by TikTok use at SDIT Muhammadiyah Cepiring Kendal. A descriptive qualitative approach was employed involving sixth-grade teachers, TikTok user students, and parents selected through purposive sampling. Data were collected through interviews, observations, and documentation, then analyzed using the Miles, Huberman, and Saldana model, while data validity was ensured through source and method triangulation. The findings indicate that TikTok influences students' character development, particularly discipline, religiosity, and social care. Discipline was the most affected value, reflected in poor time management and delayed schoolwork. Religious character declined through reduced consistency in worship, while social care weakened as students showed less interaction and concern for others. Teachers addressed these challenges through character habituation, supervision of social media use, guidance, and collaboration with parents. Despite these challenges, TikTok can also promote creativity and digital literacy when used responsibly.